2013
DOI: 10.3109/0886022x.2013.830224
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of volume status and arterial stiffness in chronic kidney disease

Abstract: Aim: There is limited information about arterial stiffness in chronic kidney disease (CKD) which is an independent risk factor for cardiovascular events. Pulse wave velocity (PWV), augmentation index (AIx) are using to determine arterial stiffness. We aimed to study PWV, AIx, volume status in patients with stage 3B-5 CKD and continuous ambulatory peritoneal dialysis (CAPD). Methods: Sixty-six stage 3B-5 CKD patients, 21 CAPD patients, 34 healthy controls were included. Pulse wave velocity, AIx, volume status w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
2
11
1
Order By: Relevance
“…They showed that fluid accumulates during the interdialytic period and contributes to increased blood pressure (15). Overhydration, has also been linked with arterial stiffness (12) and left ventricular dysfunction (13) and is strongly associated with poor cardiovascular outcomes Consistent with the literature, our study revealed that ultrafiltration volume and overhydration frequency were positively correlated with PWv and AI. As similar, Safar ME showed that interdialytic weight gain and hypervolemia are associated with increased aortic PWV (16).…”
Section: Discussionsupporting
confidence: 90%
“…They showed that fluid accumulates during the interdialytic period and contributes to increased blood pressure (15). Overhydration, has also been linked with arterial stiffness (12) and left ventricular dysfunction (13) and is strongly associated with poor cardiovascular outcomes Consistent with the literature, our study revealed that ultrafiltration volume and overhydration frequency were positively correlated with PWv and AI. As similar, Safar ME showed that interdialytic weight gain and hypervolemia are associated with increased aortic PWV (16).…”
Section: Discussionsupporting
confidence: 90%
“…Arterial pulse wave velocity and pulse propagation time play an important clinical role in defining patients under high cardiovascular risk, such as coronary artery disease and chronic dialysis patients (9-12). Arterial pulse wave velocity is inversely correlated with pulse propagation time, depending on age, heart rate, and variation in blood pressure level, such as systolic blood pressure and pulse pressure (8, 13), as shown in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse wave velocity and/or arterial stiffness is well known as a predictive risk factor for cardiovascular events in patients on hemodialysis (3-6, 12, 21). However, the effect of acute hemodialysis on pulse wave velocity is conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have linked these 2 processes [57, 58], others failed to confirm this [59, 60] with some suggesting that blood pressure [61] and fluid overload [62] are more important determinants of arterial stiffness. We did not find any association between baseline levels biomarker of inflammation and vascular health and changes in PWV over a 6-month period.…”
Section: Discussionmentioning
confidence: 99%